Beer Potomania: Why Initial Fluid Resuscitation May Be Harmful - Zhuo Lin Yu; Lisa Fisher (Case Reports in Nephrology)
Beer potomania is one of the less common causes of hyponatremia that we encounter. Patients usually have a recent history of binge drinking along with poor diet. The low solute content in alcoholic beverages limits daily urine output, and ingestion of extra fluid will cause dilutional hyponatremia as a result. Blindly providing intravenous fluid without an underlying cause of the hyponatremia can be detrimental, such as in patients with beer potomania. In our case, a patient presented to the emergency department due to poor oral intake from jaw pain and was found to be hyponatremic from alcohol intake. He initially received 2 liters of fluid, which caused overcorrection of his sodium, requiring more free water to lower his sodium as a result.